Genetic variants in sex hormone pathways and the risk of type 2 diabetes among African American, Hispanic American, and European American postmenopausal women in the US: 在非裔美国、西班牙裔美国以及在欧裔美国绝经后妇女中性激素途径的遗传变异与2型糖尿病风险. Issue 6 (6th April 2018) - Goto, Atsushi; Chen, Brian H.; Chan, Kei‐hang K.; Lee, Cathy; Nelson, Sarah C.; Crenshaw, Andrew; Bookman, Ebony; Margolis, Karen L.; Sale, Michèle M.; Ng, Maggie C.Y.; Reiner, Alexander P.; et al.
Abstract: Background: Sex hormones are implicated in the development of diabetes. However, whether genetic variations in sex hormone pathways (SHPs) contribute to the risk of type 2 diabetes mellitus (T2DM) remains to be determined. This study investigated associations between genetic variations in all candidate genes in SHPs and T2DM risk among a cohort of women participating in the Women's Health Initiative (WHI). Methods: Single nucleotide polymorphisms (SNPs) located within 30 kb upstream and downstream of SHP genes were comprehensively examined in 8180 African American, 3498 Hispanic American, and 3147 European American women in the WHI. In addition, whether significant SNPs would be replicated in independent populations was examined. Results: After adjusting for age, region, and ancestry estimates and correcting for multiple testing, seven SNPs were significantly associated with the risk of T2DM among Hispanic American women were identified in the progesterone receptor ( PGR ) gene, with rs948516 showing the greatest significance (odds ratio 0.67; 95% confidence interval 0.57–0.78; P  = 8.8 × 10 −7 ; false discovery rate, Q  = 7.8 × 10 −4 ). These findings were not replicated in other ethnic groups in the WHI or in sex‐combined analyses in replication studies. Conclusion: Significant signals were identified implicating the PGR gene in T2DM development in Hispanic American women in the WHI, which are consistent with genome‐wide association studies findings linking PGR to glucose homeostasis. Nevertheless, the PGR SNPs–T2DM association was not statistically significant in other ethnic populations. Further studies, especially sex‐specific analyses, are needed to confirm the findings and clarify the role of SHPs in T2DM. Abstract : Highlights In investigating the role of genetic variations in sex hormone pathways and the risk of diabetes, this study found a significant signal in the progesterone receptor ( PGR ) gene in Hispanic American women. However, this finding was not replicated in other populations. The data suggest the need for further studies, especially sex‐specific analyses, to confirm the findings of the present study and clarify the role of sex hormone pathways in type 2 diabetes mellitus.